DIRECT INSTRUCTION MODEL ON WRITING SKILLS IN ENGLISH SUBJECTS - Marpaung, Devi Annisa; S, Sarma Dewi Kemala; Ezir, Ely (CV. AFDIFAL MAJU BERKAH, 2024)
This research is motivated by English language learning which is still not optimal. The low interest of students in learning to write Indonesian causes students with special needs to express their ideas in written form. And this is supported by the results of the Mid-Semester Assessment (MSA) which are still unsatisfactory for many students. So researchers conducted research using the Direct Instruction model. The aim of the research was to determine the effect of the Direct Teaching model on the English theme writing skills of fifth grade students at SD N 14 Koto Baru. This type of research was carried out using quantitative research methods, design in the form of Pre-Experimental Designs type One-Group Pretest-Posttest Design. The research was conducted at SD N 14 Koto Baru. This research was carried out in the even semester (II) of the 2020/2021 academic year, the research sample was 35 class V students. Based on the results of the Wilcoxon sign rank test, a significance value of 0.000<0.05 was obtained. It can be concluded that there is an influence of the Direct Teaching model on the English theme writing skills of fifth grade students at SD N 14 Koto Baru. Based on research, the Direct instruction model has a good influence on writing skills in English subjects.